Ephemeral Ponds: Are They the Dominant Source of Depression‐Focused Groundwater Recharge?. Issue 3 (20th March 2020) - Bam, Edward K. P.; Ireson, Andrew M.; van der Kamp, Garth; Hendry, Jim M.
Abstract: Depression‐focused recharge is a concept proposed to explain groundwater recharge in the prairie regions of North America. Topographic depressions in this hummocky landscape collect blowing snow and snowmelt, and occasional runoff during rainfall events. Wetland ponds that form in these depressions lose water to evaporation and infiltration. Some of this infiltration contributes to groundwater recharge, both to shallow aquifers in the weathered near‐surface, and to underlying confined intertill aquifers. Here we focus on understanding recharge to the confined aquifers, which supply water for farms and rural communities. The isotopic composition of water in these aquifers shows little or no evaporative enrichment and is inconsistent with the average isotopic composition of the ponds. This observation appears to contradict the depression‐focused recharge model. In this field study, we examine the isotopic composition of diverse types of wetland ponds and groundwater at the St. Denis National Wildlife Area, Saskatchewan, Canada. We use hydraulic head data to identify potential recharge and discharge ponds. Water in permanent recharge ponds that do not dry out every year have distinctly different isotopic signatures from the aquifers, suggesting that they cannot be the dominant source of recharge. Water in ephemeral recharge ponds, which are small and dry out quickly, have isotopic signatures identical to those of aquifers. We propose that ephemeral recharge ponds are the dominant source of depression‐focused groundwater recharge in the prairies. We discuss why permanent recharge ponds may not be the main source of groundwater recharge and summarize our findings in a revised conceptual model. Plain Language Summary: Prairie wetland ponds have been identified as the primary sources of water for groundwater aquifers in the Northern Glaciated Prairie Plains of North America. The ponds, however, are diverse in their interactions with the subsurface and with one another. Our challenge was to compare the isotopic signature of groundwater with the range of isotopic signatures of the wetlands to determine which wetland ponds were the dominant source of groundwater recharge. Our study at St. Denis, Saskatchewan, a typical prairie setting, used hydrometric measurements and water isotopes. We found that groundwater is replenished from all recharge ponds but that ephemeral ponds—temporary ponds that dry out every year and typically disappear in spring—play the dominant role in groundwater replenishment. These ponds are abundant but seasonally short lived, losing mostly all their water by early summer to infiltration and plant transpiration. We summarize this in a revised conceptual model called the ephemeral wetland pond‐focused recharge model. Key Points: Not all ponds provide groundwater recharge in glaciated North American Prairie Plains Groundwater recharge occurs mostly in the spring Ephemeral ponds in surface depressions are the main source of depression‐focused groundwater recharge